Cell type diversity in scallop adductor muscles revealed by single-cell RNA-Seq - Sun, Xiujun; Li, Li; Wu, Biao; Ge, Jianlong; Zheng, Yanxin; Yu, Tao; Zhou, Liqing; Zhang, Tianshi; Yang, Aiguo; Liu, Zhihong (Genomics (San Diego, Calif.), 2021)
Studies on cell atlas in marine invertebrates provide a better understanding of cell types, stem cell maintenance, and lineages of cell differentiation. To investigate the molecular features of various cell types in molluscan muscles, we performed single-cell RNA sequencing (scRNA-seq) to map cell types in scallop adductor muscles. We uncovered the cell type-specific features of 20 cell clusters defined by the expression of multiple specific molecular markers. These cell clusters are mainly classified into four broad classes, including mesenchymal stem cells, muscle cells, neurons, and haemolymph cells. In particular, we identified a diverse repertoire of neurons in the striated adductor muscle, but not in the smooth muscle. We further reconstructed the cell differentiation events using all the cell clusters by single-cell pseudotemporal trajectories. By integrating dual BrdU-PCNA immunodetection, neuron-specific staining and electron microscopy observation, we showed the spatial distribution of mesenchymal stem cells and neurons in striated adductor muscle of scallops. The present findings will not only be useful to address the cell type-specific gene expression profiles in scallop muscles, but also provide valuable resources for cross-species comparison of marine organisms. •RNA sequencing at the single-cell level sheds light on cell-type diversity in scallop muscles.•The unique features of 20 cell clusters are characterized by the specific markers.•A diverse repertoire of neurons is found in the striated adductor muscle.•Cell differentiation events are constructed by the pseudotemporal trajectories.•The rich resource will lead for a better understanding of the complex muscle biology in non-model species.